Species, taxonomic, and functional group diversities of terrestrial mammals at risk under climate change and land‐use/cover change scenarios in Mexico. (13th September 2022) - Ureta, Carolina; Ramírez‐Barrón, Mercedes; Sánchez‐García, Edgar Andrés; Cuervo‐Robayo, Angela P.; Munguía‐Carrara, Mariana; Mendoza‐Ponce, Alma; Gay, Carlos; Sánchez‐Cordero, Víctor
Abstract: There is a need to revise the framework used to project species risks under climate change (CC) and land‐use/cover change (LUCC) scenarios. We built a CC risk index using the latest Intergovernmental Panel on Climate Change framework, where risk is a function of vulnerability (sensitivity and adaptive capacity), exposure, and hazard. We incorporated future LUCC scenarios as part of the exposure component. We combined a trait‐based approach based on biological characteristics of species with a correlative approach based on ecological niche modeling, assigning risk scores to species, taxonomic (orders), and functional (trophic, body size, and locomotion) groups of terrestrial mammals occurring in Mexico. We identified 15 species projected to lose their climatic suitability. Of the 11 taxonomic orders, Eulipotyphla, Didelphimorphia, Artiodactyla, and Lagomorpha had the highest risk scores. Of the 19 trophic groups, piscivores, insectivores under canopy, frugivores–granivores, herbivores browser, and myrmecophagous had the highest risk scores. Of the five body‐sized groups, large‐sized species (>15 kg) had highest risk scores. Of the seven locomotion groups, arboreal and semi‐aquatics had highest risk scores. CC and LUCC scenarios reduced suitable areas of species potential distributions by 37.5% (with CC), and 51% (with CC and LUCC) under a limited full‐dispersal assumption. Reductions in suitable areas of species potential distributions increased to 50.2% (with CC), and 52.4% (with CC and LUCC) under a non‐dispersal assumption. Species‐rich areas (>75% species) projected 36% (with CC) and 57% (with CC and LUCC) reductions in suitability for 2070. Shifts in climatic suitability projections of species‐rich areas increased in number of species in northeast and southeast Mexico and decreased in northwest and southern Mexico, suggesting important species turnover. High‐risk projections under future CC and LUCC scenarios for species, taxonomic, and functional group diversities, and species‐rich areas of terrestrial mammals highlight trends in different impacts on biodiversity and ecosystem function. Abstract : We combined trait‐based and correlative approaches to assign risks to species, taxonomic orders, and functional groups of terrestrial mammals in Mexico, under climate change (CC) and land‐use/cover change (LUCC) scenarios. Risk scores were obtained as a function of vulnerability, exposure, and hazard, using the latest Intergovernmental Panel on Climate Change framework. Overall, species (20), taxonomic orders (Eulipotyphla, Didelphimorphia, Artiodactyla, and Lagomorpha), and functional groups (large‐sized species >15 kg, piscivores, insectivores‐under‐canopy, frugivores–granivores, herbivores–browser, myrmecophagous, arboreal, and semi‐aquatic species) showed highest risk. Species‐rich areas projected 36% (with CC) and 57% (with CC and LUCC) reductions in suitability with potential impacts on biodiversity and ecosystem function.